Quantitative Measurement of Worker Protection from a Combined Perception of Occupational Safety and Health in a Graphic Advertising Company in Lima-Peru, 2021 - Godoy Martínez, Manuel Rómulo (2022)
The Occupational Health and Safety Management System (OHSMS) in the company under study was found to be deficient. The objective of this study is to identify which factors of an OHSMS are related to worker protection. For this descriptive and correlational study with a non-experimental cross-sectional design, data was collected using a survey addressed to 46 workers in June 2020. The result determined that there are 27 occupational risks affecting worker protection and the company; a Worker Protection Index (WPI) of 68% related to significant factors of the OHMSMS was also determined. It is concluded that the control measures on safe working environment, cleaning and maintenance and available common areas are the most significant factors related to worker protection in terms of reducing hazards, occupational risks, accidents and diseases. It is recommended that strategies be established to encourage worker commitment and participation.